2016
DOI: 10.3758/s13414-016-1108-5
|View full text |Cite
|
Sign up to set email alerts
|

In search of the focus of attention in working memory: 13 years of the retro-cue effect

Abstract: The concept of attention has a prominent place in cognitive psychology. Attention can be directed not only to perceptual information, but also to information in working memory (WM). Evidence for an internal focus of attention has come from the retro-cue effect: Performance in tests of visual WM is improved when attention is guided to the testrelevant contents of WM ahead of testing them. The retro-cue paradigm has served as a test bed to empirically investigate the functions and limits of the focus of attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

50
365
7
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(432 citation statements)
references
References 139 publications
(243 reference statements)
50
365
7
10
Order By: Relevance
“…These results suggest that participants likely shifted their attention to the cued location to help maintain the prioritized information in VWM. The results also are consistent with recent research on the retro-cue paradigm suggesting that items can be retrospectively selected in VWM via covert shifts of attention to items during the delay period (Griffin & Nobre, 2003;Stokes & Nobre, 2011;Souza & Oberauer, 2016). Similar to the pre-cue condition, the PLR results from the retro-cue condition suggest that early in the delay participants maintained attention on central fixation (or attention was split to both sides of the screen), but after the presentation of the retro-cue participants covertly shifted their attention to the cued location to select and maintain the cued item in VWM.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results suggest that participants likely shifted their attention to the cued location to help maintain the prioritized information in VWM. The results also are consistent with recent research on the retro-cue paradigm suggesting that items can be retrospectively selected in VWM via covert shifts of attention to items during the delay period (Griffin & Nobre, 2003;Stokes & Nobre, 2011;Souza & Oberauer, 2016). Similar to the pre-cue condition, the PLR results from the retro-cue condition suggest that early in the delay participants maintained attention on central fixation (or attention was split to both sides of the screen), but after the presentation of the retro-cue participants covertly shifted their attention to the cued location to select and maintain the cued item in VWM.…”
Section: Discussionsupporting
confidence: 81%
“…A typical finding is that retro-cues enhance performance relative to neutral cues (see Stokes & Nobre, 2011 for a review). Similar to the attention-based rehearsal hypothesis, it is assumed that with both spatial pre-and retro-cues attention covertly shifts to the prioritized location leading to enhanced processing (possibly via a number of different mechanisms; see Souza & Oberauer, 2016 for a review).…”
mentioning
confidence: 99%
“…Initial support for a more dynamic view of working memory representations comes from studies demonstrating that attentional cues presented during a working memory delay (retro-cues) can strongly facilitate performance for cued items (Griffin and Nobre, 2003; Landman et al, 2003; for review, see Souza and Oberauer, 2016). To date, however, this work has focused predominantly on spatial and/or object-based attentional influences.…”
Section: Discussionmentioning
confidence: 99%
“…For example, attentional cues presented during the retention interval (retro-cues) facilitate subsequent responses about the cued item (Griffin and Nobre, 2003; Landman et al, 2003; Pertzov et al, 2013; Souza and Oberauer, 2016). These studies have thus demonstrated that spatial and/or object-based attentional biases continue to operate during working memory and have led to the view that, among several items in working memory, a subset of the items (usually one), can be in a “prioritized state” (Cowan, 1988; Oberauer, 2002) (i.e., in the “focus of attention”).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on spatial attention in VSTM (see overview in Souza & Oberauer, 2016) may provide inspiration for the mechanisms underlying feature-based retro-cueing. One set of accounts suggests that retro-cues protect visual information from time-based decay or interference.…”
Section: Discussionmentioning
confidence: 99%